Protective glaze, marble slab and preparation method thereof

By using raw materials such as high-temperature fuses, low-temperature fuses, dolomite and wollastonite in the protective glaze of marble slabs, the problem of existing protective glazes being easily leveled during high-temperature firing is solved, and the three-dimensional effect and natural texture of marble slabs are improved.

CN119263639BActive Publication Date: 2025-04-08GUANGDONG NEWPEARL CERAMIC GRP CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411814195.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-08
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

The existing protective glaze is easy to level when fired at high temperature, resulting in the depressed texture not three-dimensional and fine enough, which cannot meet customers' needs for the texture of marble slabs.

Method used

The protective glaze prepared by combining high-aluminum fuses with low-temperature fuses, dolomite and wollastonite is used to improve the high-temperature viscosity and sintering degree of the glaze, prevent leveling and maintain the three-dimensional effect of the pattern layer.

Benefits of technology

It realizes the three-dimensional shape of the glaze during high-temperature firing, enhances the three-dimensional effect and natural texture of marble slabs, and meets customers' needs for high-quality marble slabs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263639B_ABST
    Figure CN119263639B_ABST
Patent Text Reader

Abstract

The invention relates to the field of ceramic technology, and discloses a protective glaze, a marble plate and a preparation method thereof. The raw materials for preparing the protective glaze include, by weight, 20 to 24 parts of albite, 9 to 11 parts of kaolin, 7 to 9 parts of dolomite, 3 to 4 parts of strontium carbonate, 3.5 to 4.5 parts of zinc oxide, 3.5 to 4.5 parts of low-temperature frit, 25 to 31 parts of high-aluminum frit, 8 to 10 parts of quartz powder, and 2 to 3 parts of wollastonite. The protective glaze is composed of special raw materials, especially the combination of high-aluminum frit and low-temperature frit, dolomite and wollastonite, to obtain a glaze with a relatively high-temperature viscosity. The glaze will not basically flow during the firing process, and maintain a molding effect close to the initial shape. When applied to a marble plate with a concave texture, the concave texture formed by the pattern layer can be kept in a concave or convex state, thereby having a better three-dimensional effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramics, and in particular to a protective glaze, a marble plate and a preparation method thereof. Background Art

[0002] The surface of natural stone has a soft gloss and has natural textures with different depths and sizes, showing a natural high quality. The popular tiles imitating natural marble textures in the current market are usually prepared by silk screen technology or by sinking ink technology. The production line equipment of silk screen technology is complex and costly, and it is difficult to be promoted and applied. When prepared by sinking ink technology, a pattern layer with sunken lines is usually formed by sinking ink, and then a protective glaze is applied on the surface of the pattern layer to obtain a three-dimensional marble texture effect. However, since the protective glaze layer set on the surface is usually a low-temperature glaze, it is easy to flow flat during high-temperature firing due to its low viscosity at high temperature, resulting in the texture of the sunken lines not being three-dimensional and fine enough, especially after the subsequent soft polishing process, the three-dimensional effect of the lines is further weakened, resulting in a large gap with the surface effect of real stone, which cannot meet customer needs. It can be seen that the existing technology still needs to be improved and improved. Summary of the invention

[0003] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a protective glaze, a marble slab and a preparation method thereof, aiming to solve the defect that the existing protective glaze is easy to level during high-temperature firing, and to make the obtained slab have a soft light, three-dimensional and delicate stone texture.

[0004] In order to achieve the above object, the present invention adopts the following technical solutions:

[0005] A protective glaze, wherein the raw materials for preparing the protective glaze include, by weight: 20-24 parts of albite, 9-11 parts of kaolin, 7-9 parts of dolomite, 3-4 parts of strontium carbonate, 3.5-4.5 parts of zinc oxide, 3.5-4.5 parts of low-temperature frit, 25-31 parts of high-aluminum frit, 8-10 parts of quartz powder, and 2-3 parts of wollastonite.

[0006] In the protective glaze, the raw materials for preparing the protective glaze also include 8 to 10 parts of corundum powder.

[0007] In the protective glaze, the mass ratio of SiO2 to Al2O3 is (1.9-2.6):1.

[0008] In the protective glaze, the mass percentage of CaO is 5.4-7.0%.

[0009] In the protective glaze, the chemical composition of the high-alumina frit includes, by mass percentage, SiO2 45.5-50.6%, Al2O3 18-22%, CaO 6.3-7.5%, MgO 2-2.7%, K2O 3.5-4.5%, Na2O 1.4-1.9%, BaO 9-11%, ZnO 4-5%, SrO 1.3-1.8%, and the rest are ignition loss and impurities.

[0010] In the protective glaze, the chemical composition of the low-temperature frit includes, by mass percentage: SiO2 57-63%, Al2O3 7.7-9%, CaO 10-12.5%, MgO 0.5-0.9%, K2O 6.6-7.8%, Na2O 0.5-0.9%, ZnO 9-12%, and the rest is ignition loss and impurities.

[0011] A marble slab comprises a body, a bottom glaze layer, a top glaze layer, a pattern layer and a protective glaze layer, wherein the protective glaze layer is prepared by using the protective glaze as described above; the thermal expansion coefficient of the bottom glaze layer at 400°C is (8.2-8.4)×10 -6 / ℃.

[0012] In the marble slab, the raw materials for preparing the surface glaze layer include, by weight: 42 to 47 parts of potassium-sodium aqueous abrasive, 9 to 11 parts of nepheline, 8 to 10 parts of kaolin, 10 to 14 parts of quartz, 6.5 to 8.5 parts of wollastonite, 6.5 to 8.5 parts of calcined alumina, 3 to 5 parts of medium-temperature frit, and 5 to 6 parts of zirconium silicate.

[0013] In the marble slab, the chemical composition of the medium-temperature frit includes, by mass percentage, SiO2 53-59%, Al2O3 10.5-13.5%, CaO 10-12%, MgO 1-1.6%, K2O 4.5-5.5%, Na2O 0.7-1.3%, BaO 6.8-8%, ZnO 4.5-5.5%, and the rest are ignition loss and impurities.

[0014] A method for preparing a marble slab, wherein the method is used to prepare the marble slab as described above, and the method comprises the following steps:

[0015] preparing a green body layer;

[0016] Applying a base glaze layer glaze on the body layer to obtain a base glaze layer;

[0017] Applying a top glaze layer glaze on the surface of the base glaze layer to obtain a top glaze layer;

[0018] inkjet printing colored ceramic ink and matte engraving ink on the surface of the glaze layer to obtain a pattern layer;

[0019] Applying protective glaze on the surface of the pattern layer to obtain a protective glaze layer;

[0020] Firing at 1150°C for 40 min to obtain a semi-finished product;

[0021] The semi-finished product is softly polished to a glossiness of 35°~55° to obtain a marble slab.

[0022] Beneficial effects:

[0023] The invention provides a protective glaze, a marble slab and a preparation method thereof. The protective glaze is composed of special raw materials, especially a combination of high-aluminum frit and low-temperature frit, dolomite and wollastonite, so as to obtain a glaze with relatively high high-temperature viscosity. The glaze basically does not level during the firing process, and maintains a molding effect close to the initial shape. When applied to a marble slab with a concave texture, the concave texture formed by a pattern layer can be kept in a concave or convex state, thereby having a better three-dimensional effect. At the same time, the protective glaze has soft light transmittance, can make the brick surface have a natural marble texture, and has a better viewing effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a physical picture of Example 4.

[0025] Figure 2 This is a physical picture of Example 5.

[0026] Figure 3 This is a physical picture of Example 6.

[0027] Figure 4 This is a physical picture of Comparative Example 1.

[0028] Figure 5 This is a physical picture of Comparative Example 2.

[0029] Figure 6 This is a physical picture of Comparative Example 3.

[0030] Figure 7 This is a physical picture of Comparative Example 4. DETAILED DESCRIPTION

[0031] The present invention provides a protective glaze, a marble plate and a preparation method thereof. To make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail with reference to the following embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0032] The present invention provides a protective glaze. The raw materials for preparing the protective glaze include, by weight, 20-24 parts of albite, 9-11 parts of kaolin, 7-9 parts of dolomite, 3-4 parts of strontium carbonate, 3.5-4.5 parts of zinc oxide, 3.5-4.5 parts of low-temperature frit, 25-31 parts of high-aluminum frit, 8-10 parts of quartz powder, and 2-3 parts of wollastonite. The protective glaze is composed of special raw materials, especially the combination of high-aluminum frit and low-temperature frit, dolomite and wollastonite, to obtain a glaze with relatively high high-temperature viscosity. Among them, the added high-aluminum frit can reduce the silicon-aluminum ratio, and the high calcium oxide content introduced by dolomite and wollastonite can effectively improve the high-temperature sintering degree of the glaze, avoid the difficulty of melting reaction when the aluminum content is increased, increase the high-temperature viscosity of the glaze, and no leveling phenomenon occurs during the high-temperature firing process. The molding effect close to the initial shape can be maintained. When applied to marble slabs with concave textures, the concave texture formed by the pattern layer can be kept in a concave or convex state, with a better three-dimensional effect; in addition, the added low-temperature frit has a fluxing effect, which can improve the sintering degree of the glaze, has a good anti-fouling effect, and can improve the color uniformity of the glaze, so that the protective glaze has a soft light-transmitting effect, and can make the brick surface have a natural marble texture, and the ornamental effect is better.

[0033] The protective glaze of the above raw material components has a high high temperature viscosity, which is specifically manifested in that the glaze will not collapse substantially after being fired at a temperature as high as 1200°C, and the height and width of the glaze surface change little. The following is an example of the protective glaze:

[0034] Example 1

[0035] According to weight proportions, 24 parts of albite, 9 parts of kaolin, 7 parts of dolomite, 3 parts of strontium carbonate, 3.5 parts of zinc oxide, 3.5 parts of low-temperature frit, 31 parts of high-aluminum frit, 8 parts of quartz powder and 2 parts of wollastonite are taken as raw materials for preparing protective glaze, and then auxiliary agents are added in a ratio of 100:38 of protective glaze raw materials: auxiliary agents, and the protective glaze is mixed by ball milling to obtain the protective glaze, and the protective glaze is formed into a cylinder with a diameter of 10 mm and a height of 5 mm on a carrier plate, and fired at 1200°C for 45 min. The height of the cylinder after firing is measured to be 4.53 mm and the diameter is 10.03 mm.

[0036] Example 2

[0037] In terms of weight, 20 parts of albite, 11 parts of kaolin, 9 parts of dolomite, 4 parts of strontium carbonate, 4.5 parts of zinc oxide, 4.5 parts of low-temperature frit, 25 parts of high-aluminum frit, 10 parts of quartz powder and 3 parts of wollastonite are used as raw materials for preparing the protective glaze. The rest are the same as in Example 1. After firing, the height of the cylinder is measured to be 4.39 mm and the diameter is 10.21 mm.

[0038] Example 3

[0039] In terms of weight, 22 parts of albite, 10 parts of kaolin, 8 parts of dolomite, 3.5 parts of strontium carbonate, 4 parts of zinc oxide, 4 parts of low-temperature frit, 28 parts of high-aluminum frit, 9 parts of quartz powder and 2.5 parts of wollastonite are used as raw materials for preparing the protective glaze. The rest are the same as in Example 1. After firing, the height of the cylinder is measured to be 4.47 mm and the diameter is 10.10 mm.

[0040] It can be seen from this that the protective glaze with the above-mentioned raw material components will not collapse or level when fired at a temperature within 1200°C. It can be determined that its high-temperature viscosity is relatively high. Therefore, when it is used as a protective glaze for concave textures, it will not level during the high-temperature firing process, thereby avoiding the concave textures formed by the engraving ink from being filled, thereby ensuring that the brick surface has a better three-dimensional effect.

[0041] When the protective glaze lacks high-aluminum frit, even if the other raw material components are the same as those in Example 3, it is found that the height of the cylinder after firing is only 1.7 mm. When the protective glaze lacks dolomite and high-aluminum frit, the protective glaze is basically in a level state after firing, and its height is only 0.8 mm. This is mainly due to the fact that high-aluminum frit and dolomite have a great influence on the silicon-aluminum ratio of the glaze and the content of calcium oxide.

[0042] In the aforementioned protective glaze, the glaze can have a higher high-temperature viscosity by combining the raw material components. The high-aluminum frit can increase the content of aluminum oxide in the glaze, but since the aluminum oxide does not exist in the form of crystals, its wear resistance and scratch resistance are not significantly improved. For example, the protective glaze described in Example 3 has a wear resistance of only level 3 after firing, which is difficult to meet the use needs of consumers. In this regard, as a further improvement, 8 to 10 parts of corundum powder are added to the aforementioned protective glaze. The corundum powder is high-purity corundum powder, and its aluminum oxide content exceeds 99%. The average particle size of the corundum powder is less than 10 μm, so the corundum powder can be evenly dispersed in the protective glaze glaze, and after firing, it exists in the corundum crystal phase, thereby improving the wear resistance of the protective glaze. For example, 9 parts of corundum powder are added to the protective glaze raw material in Example 3, and its wear resistance can be improved to level 4 after firing, and its transmittance is 43%. It can be seen that the corundum powder can greatly improve the wear resistance and scratch resistance of the protective glaze, and can enable the protective glaze to maintain good light transmittance.

[0043] The aforementioned protective glaze, when used as a protective glaze for marble slabs, should not only have a high high temperature viscosity, but also have a soft light transmission effect, so that the pattern texture presents a texture like natural marble. Among them, since the quality of SiO2, Al2O3 and CaO will affect the high temperature viscosity and light transmission effect of the protective glaze, for example, when the silicon-aluminum ratio is too low, the aluminum content is high, the melting temperature will rise, and the viscosity will increase in the molten state. Although the three-dimensional effect will be more prominent, it is easy to make the glaze unable to burn through and difficult to melt flat, and it is easy to form defects at the bottom and pores on the surface, resulting in rough concave and convex textures, and unable to form the natural texture of marble. In this regard, in a preferred embodiment, by adjusting the raw material components in the protective glaze, the mass ratio of SiO2 to Al2O3 is (1.9-2.6):1, and the mass percentage of CaO is 5.4-7.0%, the protective glaze can have a suitable high temperature viscosity, a moderate light transmission effect, and a natural texture with soft light.

[0044] As a high-aluminum frit that has an important influence on the high-temperature viscosity of the protective glaze, its chemical composition will directly affect the ratio of silicon and aluminum in the protective glaze. As a preferred embodiment, the chemical composition of the high-aluminum frit includes by mass percentage: SiO245.5~50.6%, Al2O318~22%, CaO 6.3~7.5%, MgO 2~2.7%, K2O 3.5~4.5%, Na2O 1.4~1.9%, BaO 9~11%, ZnO 4~5%, SrO 1.3~1.8%, and the rest is ignition loss and impurities. The high-aluminum frit with this chemical composition can better improve the high-temperature viscosity of the protective glaze, prevent the glaze from leveling during firing, and improve the molding effect after sintering.

[0045] Preferably, the chemical composition of the high-alumina frit includes, by mass percentage, SiO2 48.0%, Al2O3 20.0%, CaO 6.9%, MgO 2.3%, K2O 4.0%, Na2O 1.6%, BaO 10.0%, ZnO 4.6%, SrO 1.6%, and the rest are ignition loss and impurities.

[0046] As another preferred embodiment, the chemical composition of the low-temperature frit includes, by mass percentage, SiO2 57-63%, Al2O3 7.7-9%, CaO 10-12.5%, MgO 0.5-0.9%, K2O 6.6-7.8%, Na2O 0.5-0.9%, ZnO 9-12%, and the rest is ignition loss and impurities. The low-temperature frit of this chemical composition has a high calcium content, has a fluxing effect, and can improve the sintering degree of the glaze.

[0047] Preferably, the chemical composition of the low-temperature frit includes, by mass percentage, SiO2 60.0%, Al2O3 8.4%, CaO 11.3%, MgO 0.7%, K2O 7.2%, Na2O 0.7%, ZnO 10.6%, and the rest are loss on ignition and impurities.

[0048] The second aspect of the present invention also provides a marble slab, which includes a body, a base glaze layer formed on the body, a surface glaze layer formed on the base glaze layer, a pattern layer printed on the surface glaze layer by inkjet, and a protective glaze layer sprayed on the pattern layer, wherein the pattern layer is a layered structure with a color pattern and a texture formed by printing a color ceramic ink and a matte engraving ink, and the matte engraving ink includes the following components in parts by weight: 30 to 40 parts of an engraving agent, 52 to 64 parts of a solvent, and 5 to 9 parts of an auxiliary agent (including 4 to 8 parts of a dispersant, 0.4 to 0.8 parts of an anti-settling agent, and 0.3 to 0.5 parts of a defoaming agent). The matte engraving ink can form a concave-convex texture with undulating dots, lines or blocks on the surface of the slab, and at the same time, combined with the pattern formed by the color ceramic ink, it has a realistic pattern texture imitating natural marble. The protective glaze layer is arranged on the pattern layer and is prepared using the protective glaze as described above. Therefore, no leveling phenomenon occurs during firing, and the concave and convex texture of the pattern layer can still maintain a good three-dimensional effect after firing, with a realistic imitation marble texture.

[0049] In a preferred embodiment, the raw materials used to form the surface glaze layer include, by weight: 42-47 parts of potassium sodium water abrasive, 9-11 parts of nepheline, 8-10 parts of kaolin, 10-14 parts of quartz, 6.5-8.5 parts of wollastonite, 6.5-8.5 parts of calcined alumina, 3-5 parts of medium-temperature frit, and 5-6 parts of zirconium silicate. The surface glaze layer raw materials use a large amount of potassium sodium water abrasive, which can improve the firing range and whiteness of the surface glaze layer, and can make the pattern texture of the pattern layer better highlighted; in addition, the wollastonite added to the raw materials of the surface glaze layer can increase the initial melting point of the glaze, facilitate exhaust, and effectively eliminate the limitation of the glaze layer that the pores are small and difficult to exhaust due to the increase in sintering degree, and optimize the "prickly heat" defect problem under fast firing conditions. In addition, its high-temperature melting characteristics also effectively reduce the amount of crystallization, maintain the uniformity of the surface glaze layer, and prevent surface defects from affecting the pattern effect.

[0050] As a preferred embodiment, the chemical composition of the medium-temperature frit added to the raw material of the surface glaze layer includes, by mass percentage, SiO2 53-59%, Al2O3 10.5-13.5%, CaO 10-12%, MgO 1-1.6%, K2O 4.5-5.5%, Na2O 0.7-1.3%, BaO 6.8-8%, ZnO 4.5-5.5%, and the rest is ignition loss and impurities. The medium-temperature frit of this chemical composition can promote the sintering performance of the glaze and enhance the bonding between the surface glaze layer and the protective glaze.

[0051] Preferably, the chemical composition of the medium-temperature frit includes, by mass percentage, SiO2 56.0%, Al2O3 12.0%, CaO 11.0%, MgO 1.3%, K2O 5.0%, Na2O 1.0%, BaO 7.4%, ZnO 5.0%, and the rest are loss on ignition and impurities.

[0052] Since the expansion coefficient of the aforementioned protective glaze is relatively small, its expansion coefficient at 400°C is (5.7-5.9)×10 -6 / ℃, so it is easy to cause the brick shape to bend downward. In this regard, in a preferred embodiment, the bottom glaze layer is prepared by raw materials with a higher expansion coefficient. Specifically, the raw materials for preparing the bottom glaze layer include, by weight: 27-33 parts of potassium and sodium feldspar powder, 8-10 parts of calcined alumina, 13-17 parts of high white ball clay, 12-16 parts of nepheline powder, 0.5-1.5 parts of dolomite, 24-30 parts of quartz powder, 0.5-1.5 parts of calcined talc powder, and 2.5-3.5 parts of calcined kaolin. The thermal expansion coefficient of the bottom glaze layer of the raw material composition at 400℃ is (8.2-8.4)×10 -6 / ℃, which can eliminate the bending of bricks caused by the small expansion coefficient of the protective glaze layer and make the brick surface smoother.

[0053] In order to further illustrate the protective glaze provided by the present invention and the marble slab using the protective glaze, the following embodiments are provided.

[0054] Example 4

[0055] A wear-resistant marble plate is made of a body layer, a bottom glaze layer, a surface glaze layer, a pattern layer and a marble protective glaze layer.

[0056] Among them, the raw materials for preparing the green body layer include, by weight: 44 parts of potassium sodium sand, 12.5 parts of kaolin, 8 parts of ball clay, 7 parts of medium-temperature sand, 6 parts of high clay, 5 parts of potassium sodium stone powder, 4 parts of diopside, 3.5 parts of silica sand, and 10 parts of polishing mud (it should be noted that the polishing mud is the waste residue and waste mud generated after polishing and grinding of ceramic tiles, and its main components are silicon oxide and aluminum oxide);

[0057] The raw materials for preparing the bottom glaze layer include, by weight: 30 parts of potassium and sodium feldspar powder, 9 parts of calcined alumina, 15 parts of high white ball clay, 14 parts of nepheline powder, 1 part of dolomite, 27 parts of quartz powder, 1 part of calcined talc powder, and 3 parts of calcined kaolin;

[0058] The raw materials for preparing the surface glaze layer include, by weight: 44.5 parts of potassium sodium water abrasive, 10 parts of nepheline, 9 parts of kaolin, 12 parts of quartz, 7.5 parts of wollastonite, 7.5 parts of calcined alumina, 4 parts of medium-temperature frit, and 5.5 parts of zirconium silicate;

[0059] In terms of weight, the raw materials for preparing the protective glaze layer include: 22 parts of albite, 10 parts of kaolin, 8 parts of dolomite, 3.5 parts of strontium carbonate, 4 parts of zinc oxide, 4 parts of low-temperature frit, 28 parts of high-alumina frit, 9 parts of quartz powder, 9 parts of corundum powder, and 2.5 parts of wollastonite.

[0060] In the protective glaze layer, the mass ratio of SiO2 to Al2O3 is 2.24:1, and the mass percentage of CaO is 6.2%.

[0061] It should be noted that the raw materials for preparing the green body, the bottom glaze layer, the top glaze layer and the protective glaze layer also include some additives or solvents, which are prior arts in the art and will not be described in detail herein.

[0062] The pattern layer is a combination of color patterns and textures formed by printing colored ceramic ink and matte engraving ink, wherein the colored ceramic ink is a conventional ceramic ink, and the matte engraving ink includes the following components by weight: 35 parts of engraving agent, 58 parts of ester solvent, 7 parts of auxiliary agent (6 parts of dispersant, 0.6 parts of anti-settling agent, 0.4 parts of defoaming agent). The engraving agent is composed of the following raw materials by weight: 21 parts of quartz, 7 parts of wollastonite, 30 parts of barium sulfate, 15 parts of barium carbonate, 13 parts of vanadium pentoxide, and 14 parts of lead metasilicate.

[0063] The preparation method of the marble slab is as follows:

[0064] preparing a green body layer;

[0065] Applying a base glaze layer glaze on the body layer to obtain a base glaze layer;

[0066] Applying a top glaze layer glaze on the surface of the base glaze layer to obtain a top glaze layer;

[0067] inkjet printing colored ceramic ink and matte engraving ink on the surface of the glaze layer to obtain a pattern layer;

[0068] Applying protective glaze on the surface of the pattern layer to obtain a protective glaze layer;

[0069] Firing at a maximum temperature of 1150°C for 40 minutes to obtain a semi-finished product;

[0070] The semi-finished product is softly polished to a glossiness of 35°-55° to obtain a marble slab. Figure 1 shown.

[0071] Example 5

[0072] A marble slab, such as Figure 2 As shown, its preparation method and raw material ratio are basically the same as those in Example 4, except that: in terms of weight, the raw materials for preparing the protective glaze layer include: 24 parts of albite, 9 parts of kaolin, 7 parts of dolomite, 3 parts of strontium carbonate, 3.5 parts of zinc oxide, 3.5 parts of low-temperature frit, 31 parts of high-aluminum frit, 10 parts of corundum powder, 8 parts of quartz powder, and 3 parts of wollastonite. In the protective glaze layer, the mass ratio of SiO2 to Al2O3 is 2.56:1, and the mass percentage of CaO is 6.82%.

[0073] Example 6

[0074] A marble slab, such as Figure 3 As shown, its preparation method and raw material ratio are basically the same as those in Example 4, except that: in terms of weight, the raw material composition for preparing the protective glaze layer includes: 20 parts of albite, 11 parts of kaolin, 9 parts of dolomite, 4 parts of strontium carbonate, 4.5 parts of zinc oxide, 4.5 parts of low-temperature frit, 25 parts of high-aluminum frit, 8 parts of corundum powder, 10 parts of quartz powder, and 2 parts of wollastonite. In the protective glaze layer, the mass ratio of SiO2 to Al2O3 is 1.98:1, and the mass percentage of CaO is 5.58%.

[0075] Comparative Example 1

[0076] A marble slab, such as Figure 4 As shown, its preparation method and raw material ratio are basically the same as those in Example 4, except that: no high-alumina frit is added to the raw materials for preparing the protective glaze layer, and the mass ratio of SiO2 to Al2O3 in the protective glaze layer is 7.55:1, and the mass percentage of CaO is 8.21%.

[0077] Comparative Example 2

[0078] A marble slab, such as Figure 5 As shown, its preparation method and raw material ratio are basically the same as those in Example 4, except that no dolomite is added to the raw materials for preparing the protective glaze layer, and in the protective glaze layer, the mass ratio of SiO2 to Al2O3 is 2.13:1, and the mass percentage of CaO is 2.2%.

[0079] Comparative Example 3

[0080] A marble slab, such as Figure 6As shown, its preparation method and raw material ratio are basically the same as those in Example 4, except that: in terms of weight, the raw material composition for preparing the protective glaze layer is: 16 parts of albite, 13 parts of kaolin, 11 parts of dolomite, 4.5 parts of strontium carbonate, 3 parts of zinc oxide, 2.5 parts of low-temperature frit, 34 parts of high-aluminum frit, 6 parts of quartz powder, 9 parts of corundum powder, and 1 part of wollastonite. In the protective glaze layer, the mass ratio of SiO2 to Al2O3 is 1.58:1, and the mass percentage of CaO is 8.83%.

[0081] Comparative Example 4

[0082] A marble slab, such as Figure 7 As shown, its preparation method and raw material ratio are basically the same as those in Example 4, except that: in terms of weight, the raw material composition for preparing the protective glaze layer is: 28.5 parts of albite, 6.5 parts of kaolin, 5 parts of dolomite, 2.5 parts of strontium carbonate, 5 parts of zinc oxide, 5.5 parts of low-temperature frit, 21 parts of high-aluminum frit, 13 parts of quartz powder, 9 parts of corundum powder, and 4 parts of wollastonite. In the protective glaze layer, the mass ratio of SiO2 to Al2O3 is 3.24:1, and the mass percentage of CaO is 3.95%.

[0083] It should be noted that in Examples 4-6 and Comparative Examples 1-4, the chemical compositions of the high-aluminum frit, the low-temperature frit and the medium-temperature frit are all the same. Among them, the chemical composition of the high-aluminum frit is calculated by mass percentage: SiO248.0%, Al2O320.0%, CaO 6.9%, MgO 2.3%, K2O 4.0%, Na2O 1.6%, BaO 10.0%, ZnO 4.6%, SrO 1.6%, and the rest is loss on ignition and impurities; the chemical composition of the low-temperature frit is calculated by mass percentage: SiO260.0%, Al2O38.4%, CaO 11.3%, MgO0.7%, K2O 7.2%, Na2O 0.7%, ZnO 10.6%, and the rest is loss on ignition and impurities; the chemical composition of the medium-temperature frit is calculated by mass percentage: SiO256.0%, Al2O312.0%, CaO 11.0%, MgO 1.3%, K2O 5.0%, Na2O 1.0%, BaO7.4%, ZnO 5.0%, the rest is loss on ignition and impurities.

[0084] Performance Testing

[0085] The performance tests of the panels prepared in Examples 4-6 and Comparative Examples 1-4 were carried out, specifically including light transmittance, stain resistance, wear resistance and surface quality, wherein the light transmittance of the protective glaze layer was tested using a transmittance meter (for light transmittance, only the transmittance of the protective glaze layer of each embodiment and comparative example could be tested, specifically, the protective glaze was fired into a glaze sheet with a diameter of not less than 20 mm and a thickness of 1 mm for testing), the surface wear resistance was tested using the method in GB / T3810.7, and the surface stain resistance and surface quality were tested using the method in GB / T3810.14-2016. The specific test results are shown in Table 1.

[0086] Table 1. Performance test results

[0087]

[0088] It can be seen from Examples 4-6 in Table 1 that the marble slabs prepared by the technical solution of the present invention have good wear resistance (up to level 4) and stain resistance (up to level 5), and the surface has undulating linear, dot-shaped, and block-shaped concave-convex textures (with strong three-dimensional and layered sense), good color, good brick shape, soft and comfortable light feeling, and excellent quality.

[0089] By comparing Example 4 and Comparative Example 1, it can be seen that when the protective glaze raw material lacks high-aluminum frit, the silicon-aluminum ratio will be too high, the flux ratio will increase, the low-temperature eutectic will be fast, and the glaze will be easy to level during high-temperature firing, thereby filling the concave texture formed by the engraving ink. At the same time, too low a temperature can easily cause overfiring, defects in the glaze surface, poor three-dimensional effect of the concave and convex texture, poor wear resistance, poor light transmittance, and dull color.

[0090] By comparing Example 4 and Comparative Example 2, it can be seen that when dolomite is lacking in the protective glaze raw materials, the calcium oxide content will be too low, the high-temperature sintering degree of the glaze will be poor, and it will be easy to fail to obtain sufficient melting reaction when the aluminum content is increased, which will easily cause raw firing, resulting in defects in the glaze surface, rough concave and convex texture, poor brick shape, and poor light transmittance and color.

[0091] By comparing Example 4 and Comparative Example 3, it can be seen that when the high-aluminum frit and dolomite account for a large proportion of the protective glaze raw materials, the silicon-aluminum ratio will be too low and the calcium oxide content will be too high. The aluminum content is high, the melting temperature will rise, and the viscosity in the molten state will increase. Although the three-dimensional effect will be more prominent, it is easy for the glaze to be unable to burn through and difficult to melt flat, and defects are easily formed at the bottom and pores are easily formed on the surface, resulting in rough concave and convex texture, reduced light transmittance and poor color, and reduced anti-fouling properties of the product surface. At the same time, the low-silicon and high-aluminum solution leads to a decrease in the stability of the internal chemical bonds, poor corrosion resistance, and high aluminum reduces the expansion coefficient, which also affects the brick shape.

[0092] By comparing Example 4 and Comparative Example 4, it can be seen that when the proportion of high-aluminum frit and dolomite in the protective glaze raw materials is small, the silicon-aluminum ratio will be too high and the calcium oxide content will be low, which will easily cause a low-temperature eutectic reaction to cause the glaze to be over-burned. In addition, since the surface layer is closed in advance due to low-temperature melting, the gas in the lower layer is difficult to discharge, and the hole defects in the bottom layer affect the pattern effect, the fineness and three-dimensional effect of the concave and convex texture of the brick surface, and the light transmittance is poor. At the same time, the high-silicon and low-aluminum solution leads to a larger expansion coefficient, which is easy to cause glaze cracking and also affects the brick shape.

[0093] It is understandable that those skilled in the art can make equivalent substitutions or changes based on the technical solution and inventive concept of the present invention, and all these changes or substitutions should fall within the protection scope of the claims attached to the present invention.

Claims

1. A protective glaze, characterized in that: The raw materials for preparing the protective glaze include, by weight: 20-24 parts of albite, 9-11 parts of kaolin, 7-9 parts of dolomite, 3-4 parts of strontium carbonate, 3.5-4.5 parts of zinc oxide, 3.5-4.5 parts of low-temperature frit, 25-31 parts of high-aluminum frit, 8-10 parts of quartz powder, and 2-3 parts of wollastonite; The chemical composition of the high-alumina frit includes, by mass percentage, SiO2 45.5-50.6%, Al2O3 18-22%, CaO 6.3-7.5%, MgO 2-2.7%, K2O 3.5-4.5%, Na2O 1.4-1.9%, BaO 9-11%, ZnO 4-5%, SrO 1.3-1.8%, and the rest are ignition loss and impurities; The chemical composition of the low-temperature frit includes, by mass percentage, SiO2 57-63%, Al2O3 7.7-9%, CaO10-12.5%, MgO 0.5-0.9%, K2O 6.6-7.8%, Na2O 0.5-0.9%, ZnO 9-12%, and the rest is ignition loss and impurities; In the protective glaze, the mass ratio of SiO2 to Al2O3 is (1.9-2.6):1; the mass percentage of CaO is 5.4-7.0%.

2. The protective glaze according to claim 1, characterized in that: The raw materials for preparing the protective glaze also include 8 to 10 parts of corundum powder.

3. A marble slab, comprising a body, a bottom glaze layer, a top glaze layer, a pattern layer, and a protective glaze layer, characterized in that: The protective glaze layer is prepared by using the protective glaze as claimed in claim 1 or 2; the thermal expansion coefficient of the base glaze layer at 400°C is (8.2-8.4)×10 -6 / ℃.

4. The marble slab according to claim 3, characterized in that: The raw materials for preparing the surface glaze layer include, by weight: 42-47 parts of potassium-sodium water abrasive, 9-11 parts of nepheline, 8-10 parts of kaolin, 10-14 parts of quartz, 6.5-8.5 parts of wollastonite, 6.5-8.5 parts of calcined alumina, 3-5 parts of medium-temperature frit, and 5-6 parts of zirconium silicate; Calculated by mass percentage, the chemical composition of the medium-temperature melt includes: SiO2 53-59%, Al2O3 10.5-13.5%, CaO 10-12%, MgO 1-1.6%, K2O 4.5-5.5%, Na2O 0.7-1.3%, BaO 6.8-8%, ZnO 4.5-5.5%, and the rest are ignition loss and impurities.

5. A method for preparing a marble slab, characterized in that: For preparing the marble slab as claimed in claim 3 or 4, the method comprises the following steps: preparing a green body layer; Applying a base glaze layer glaze on the body layer to obtain a base glaze layer; Applying a top glaze layer glaze on the surface of the base glaze layer to obtain a top glaze layer; inkjet printing colored ceramic ink and matte engraving ink on the surface of the glaze layer to obtain a pattern layer; Applying protective glaze on the surface of the pattern layer to obtain a protective glaze layer; Firing at 1150°C for 40 min to obtain a semi-finished product; The semi-finished product is softly polished to a glossiness of 35°~55° to obtain a marble slab.

Citation Information

Patent Citations

  • Soft light marble tile and preparation method thereof

    CN116178053A

  • Frit dry particles, protective glaze, three-dimensional texture soft-light glazed tile and preparation method of three-dimensional texture soft-light glazed tile

    CN117342793A